Concordance and Discordance of Mitotic Count, Ki-67 Proliferative Index and Phosphohistone H3 Count in Grading Neuroendocrine Tumors of Gastrointenstinal Tract - Humayun, Saba; Asif, Muhammad; Khadim, Muhammad Tahir; Din, Hafeez Ud; Ahsan, Farah; Rashid, Farhat (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the grades of gastrointestinal neuroendocrine tumours using World Health Organization criteria and Phosphohistone H3 mitotic index and to determine the concordance between the two methods. Study Design: Cross-sectional study. Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Mar to Oct 2019. Methodology: Forty-two (n=42) patients of either gender between the ages of 18-70 years were enrolled. All the enrolled patients were diagnosed with primary gastrointestinal neuroendocrine tumours and underwent either surgical or endoscopic resection. Tumour grades were determined using World Health Organization criteria and Phosphohistone H3mitotic index. The results obtained with both methods were compared, and the concordance rate was calculated. Results: When mitotic counts were determined through PHH3, MI resulted in a change of grade of 12 (28.6%) tumours, which were graded by the current WHO system. 11 (26.2%) were changed from grade II to grade I and 1 (2.4%) from grade I to grade I1. The agreement (concordance rate) between the two systems was moderate and statistically significant (71.4%, n=30/42, κ= 0.51, p= 0.001). Conclusion: In the present study, we observed a moderate agreement between the Ki-67 labelling index and the PPH3 mitotic index, and both correlate well with the mitotic counts. The PPH3 mitotic index demonstrated a better correlation with mitotic counts when compared with Ki-67 LI. Hence, the inference can be drawn that the mitotic index with Phosphohistone H3is associated more closely with mitosis in gastrointestinal neuroendocrine tumours.